ANALISIS DAMPAK TIPE KEPRIBADIAN FEELING DAN THINKING TERHADAP RESILIENSI AKADEMIK MAHASISWA BIMBINGAN DAN KONSELING TINGKAT AKHIR ANGJATAN 2022 UNIVERSITAS SLAMET RIYADI TAHUN 2026 - Tiana Azzahra, Helvi; Heru Sri Suryanti, Hera; Jawandi, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A Descriptive Analysis of the Impact of Feeling (F) and Thinking (T) Personality Types on Academic Resilience among Final-Year Students of the Guidance and Counseling Study Program, 2022 Cohort, Slamet Riyadi University, Surakarta, 2026 This study aims to provide a descriptive account of the impact of the Feeling (F) and Thinking (T) personality types on the academic resilience of final-year Guidance and Counseling students from the 2022 cohort at Slamet Riyadi University, Surakarta, in 2026. This research employs a descriptive qualitative method. The subjects of this study were final-year Guidance and Counseling students from the 2022 cohort who were in the process of completing their undergraduate theses. The research instruments utilized observation guidelines, interview guidelines, and documentation, which were employed in the data collection process with the subjects. The obtained data were then analyzed through several stages, including summarizing, drawing conclusions, and verification. Based on the findings of this study, it can be concluded that both personality types demonstrate good academic resilience, albeit with distinct characteristics. Students with the Thinking personality type tend to develop resilience through logical and structured approaches, whereas students with the Feeling personality type build resilience through emotional regulation and social support.